Multimodal imaging reveals a role for Akt1 in fetal cardiac development. Issue 6 (7th November 2013) - Vandoorne, Katrien; Vandsburger, Moriel H.; Weisinger, Karen; Brumfeld, Vlad; Hemmings, Brian A.; Harmelin, Alon; Neeman, Michal
Abstract: Even though congenital heart disease is the most prevalent malformation, little is known about how mutations affect cardiovascular function during development. Akt1 is a crucial intracellular signaling molecule, affecting cell survival, proliferation, and metabolism. The aim of this study was to determine the role of Akt1 on prenatal cardiac development. In utero echocardiography was performed in fetal wild‐type, heterozygous, and Akt1‐deficient mice. The same fetal hearts were imaged using ex vivo micro‐computed tomography ( μ CT) and histology. Neonatal hearts were imaged by in vivo magnetic resonance imaging. Additional ex vivo neonatal hearts were analyzed using histology and real‐time PCR of all three groups. In utero echocardiography revealed abnormal blood flow patterns at the mitral valve and reduced contractile function of Akt1 null fetuses, while ex vivo μ CT and histology unraveled structural alterations such as dilated cardiomyopathy and ventricular septum defects in these fetuses. Further histological analysis showed reduced myocardial capillaries and coronary vessels in Akt1 null fetuses. At neonatal age, Akt1‐deficient mice exhibited reduced survival with reduced endothelial cell density in the myocardium and attenuated cardiac expression of vascular endothelial growth factor A and collagen I α 1. To conclude, this study revealed a central role of Akt1 in fetal cardiac function and myocardial angiogenesis inducing fetal cardiomyopathy and reduced neonatal survival. This study links a specific physiological phenotype with a defined genotype, namely Akt1 deficiency, in an attempt to pinpoint intrinsic causes of fetal cardiomyopathies. Abstract : e00143 Akt1 −/− fetuses displayed smaller hearts and reduced fetal weight. (A and B) Ex vivo μ CT images and volume‐rendered hearts revealing reduced size with a thinner myocardium and ventricular septum with a dilated morphology in Akt1 −/− mice (B, arrowheads). (C and D) Quantification of volumes of fetal heart at E16.5 (C) and E18.5 (D), illustrates reduced Akt1 −/− myocardial volume. (E) Akt1 −/− fetuses displayed significantly lower weight at E16.5 compared to Akt1 +/+ fetuses. RV, right ventricle; LV, left ventricle; +/+, Akt1 +/+ ; +/ −, Akt1 +/− ; − / −, Akt1 −/− ; * P  < 0.05.